NAVIGATING THE DYNAMICS OF INDIAN ECONOMIC GROWTH: A CRITICAL ANALYSIS OF RECENT TAX POLICY REFORMS - Anand G, Murali (ShodhKosh: Journal of Visual and Performing Arts, 2024)
India’s economic landscape has been profoundly shaped by an evolving tax policy framework aimed at fostering growth, improving compliance, and addressing inequalities. Key reforms, such as the Goods and Services Tax (GST) and direct tax measures, have sought to streamline revenue collection and enhance the ease of doing business. Despite notable achievements, challenges persist, including fiscal deficits, compliance burdens, and equity concerns. This paper critically examines the trajectory of Indian tax policies, their impact on economic growth, and their contribution to equitable development. Drawing on empirical data and policy analyses, it identifies gaps and proposes actionable recommendations to make the system more robust and inclusive.